Weste products of steel galvanizing processes for obtaining technology of colored glazes - Вахула, Орест Миронович; Позняк, Ігор Вікторович; Солоха, Іван Володимирович; Пона, Мирон Григорович; Боровець, Зенон Іванович (Eastern-European Journal of Enterprise Technologies, 2013)
The subject of this research is glass-forming compounds pegmatite-slag of thermal pover plants-waste products of galvanizing processes based on frits. The subject of this research is colored low-melt glazes. The objective of the work is elaboration of compounds and technology obtaining colored glazes using waste products of steel galvanizing processes. Up-to-date methods of investigation (X-ray phase analysis, differential thermal analysis, flame photometry and optical electroscopy) have been used in this work. Peculiarities of the formation of slimes of steel parts galvanizing and their properties have been investigated. The processes of gas formation in the process of thermal treatment of slimes have been studied in the range of temperatures 293…1773 K. Regularities of crystallization of coloring crystal phases α-Fe2o3, ZnO•Fe2o3 and Feo•Fe2o3 that ensure obtaining colored glazes have been established. Technology of obtaining low-melt glazes of brown and cherry-brown colors based on low-melt frit without adding additional ceramic pigments with firing temperature 1343…1373 K has been elaborated. It was established, that with the increase of slime content from 10 to 30 weight % in the composition of glazes the color of coating changes from brown to cherry-brown and the purity of color increases from 31 % to 47 %. The obtained compositions of such glazes were successfully tested under the manufacturing conditions and confirmed the possibility of producing decorative oven ceramic tiles with improved decorative and maintenance properties.